Women at a reception counter - Unknown:::Creator::::::::::::
Negative shows two women talking at a counter in a reception area as another women in the foreground looks on. There is a fourth women on the phone sitting behind the desk and the wall has a sign that reads: "YWCA of the U.S.A. Leadership [Develop]ment Cen[ter]."